Primary splenic lymphoma. Case study - Leonid I. Dvoretsky; Oleg E. Lutsevich; Vasilii V. Filippov; Sergei S. Golubev; Svetlana E. Kolendo (LLC "MEDIAFORMAT", 2021)
The case of primary splenic lymphoma, the uncommon type of non-Hodgkin lymphoma presenting with prominent splenomegaly, is reported. The disease is characterized by long asymptomatic stage and splenic abscess found during splenectomy.